Fear and Trembling: Performing the Protestant Conscience in Thomas Middleton’s The Lady’s Tragedy - Snyder, Jillian (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2023)
With its glorified ghost, godly avenger, and idolatrous Tyrant, Thomas Middleton’s The Lady’s Tragedy appears to offer a thinly veiled allegory of Protestant triumphalism. Little attention has been paid, however, to how its characters do — or do not — respond to the play’s many crises of conscience. This essay sets Middleton’s tragedy against English Protestant understandings of the trembling body and vexed conscience. It demonstrates that while the play’s multiple instances of trembling seem to unsettle its Protestant triumphalism, its special effects, intended to provoke audience trembling, might nevertheless deepen playgoers’ attachment to the Protestant cause.